If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (14 + 6x) = 134 Remove parenthesis around (14 + 6x) 14 + 6x = 134 Solving 14 + 6x = 134 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 6x = 134 + -14 Combine like terms: 14 + -14 = 0 0 + 6x = 134 + -14 6x = 134 + -14 Combine like terms: 134 + -14 = 120 6x = 120 Divide each side by '6'. x = 20 Simplifying x = 20
| (-15+4)n=77 | | 2-2=3 | | 4n+12=5n+7n | | y=2/3(-6)-2 | | y=2/3(6)-2 | | 25r^2-64=0 | | y=-2/3(6)-2 | | 124+x=25-3 | | y=-2/3(3)-2 | | y=-2/3(0)-2 | | y=-2/3(-3)-2 | | y=-3/2(4)+7 | | y=-3/2(2)+7 | | 4/14=q/12 | | 5/1-x=4/3-x | | y=-3/2(0)+7 | | y=-3/2(-2)+7 | | 5(8-2x)=40 | | -2x+2x+1=9 | | y=3/2(0)+7 | | 2q=0 | | 36k^2+12k+1=0 | | y=3/2(-2)+7 | | 4(u+1)=-4u+28 | | y=3/2(-4)+7 | | 8p-40=40 | | 3y-3=58 | | y=3/2(-6)+7 | | 0=-4.9t^2+25t+12 | | (-0.2)(-0.14)= | | 13r^2+21r-10=9 | | (3y-3)(2y+2)=58 |